Ex vivo expansion and genetic manipulation of mouse hematopoietic stem cells in polyvinyl alcohol-based cultures - Khoo, HM; Meaker, GA; Wilkinson, AC (MyJove Corporation, 2023)
Self-renewing multipotent hematopoietic stem cells (HSCs) are an important cell type due to their abilities to support hematopoiesis throughout life and reconstitute the entire blood system following transplantation. HSCs are used clinically in stem cell transplantation therapies, which represent curative treatment for a range of blood diseases. There is substantial interest in both understanding the mechanisms that regulate HSC activity and hematopoiesis, and developing new HSC-based therapies. However, the stable culture and expansion of HSCs ex vivo has been a major barrier in studying these stem cells in a tractable ex vivo system. We recently developed a polyvinyl alcohol-based culture system that can support the long-term and large-scale expansion of transplantable mouse HSCs and methods to genetically edit them. This protocol describes methods to culture and genetically manipulate mouse HSCs via electroporation and lentiviral transduction. This protocol is expected to be useful to a wide range of experimental hematologists interested in HSC biology and hematopoiesis.